Pesan Dakwah tentang Nikah di Media Sosial Instagram - Nurasiah Ismail; Zainal Abidin; Uwes Fatoni (Department of Islamic Communication and Broadcasting, Faculty of Dakwah and Communication, UIN Sunan Gunung Djati Bandung, 2017)
The purpose of this research is to know the meaning of message of da'wah about marriage in social media of instagram on account of @nikahbarokah which is formulated in the question how the meaning of denotation, connotation, and myth of da'wah message about marriage in account instagram @niahbarokah ? The method used in this study is semiotics analysis in the form of data analysis that is by determining quote, interpreting quote, menyangkutkan with what is considered a valuable society with the meaning of semiotics in the form of denotation meaning, connotation meaning, the meaning of myths are considered capable to recognize the signs and messages hidden behind quote message da'wah about marriage on account instagram @niahbarokah. The result concluded that the message of da'wah about marriage posted by account manager of @nikahbarokah during October to December 2016 there are 8 quote of message of da'wah classified based on the stage of marriage is ta'aruf, marriage and post marriage in physiological aspects (sakinah), psychological (mawadah), and sociological (rahmah). In denotative post contained in the picture contains elements of images, writing words and connotative with regard to the meaning contained in denotation, and the meaning of myths relating to daily life. Tujuan penelitian ini untuk mengetahui makna pesan dakwah tentang nikah di media sosial instagram pada akun @nikahbarokah yang terumuskan di dalam pertanyaan bagaimana makna denotasi, makna konotasi dan mitos pesan dakwah tentang nikah dalam akun instagram @nikahbarokah. Metode yang digunakan dalam penelitian ini adalah analisis semiotika yang berbentuk analisis data yaitu dengan menentukan quote, menafsirkan quote, menyangkutkan dengan yang dianggap masyarakat bernilai dengan makna semiotika berupa makna denotasi, makna konotasi, makna mitos yang dianggap mampu untuk mengenali tanda dan pesan yang tersembunyi dibalik quote pesan dakwah tentang nikah pada akun instagram @nikahbarokah. Hasil dari penelitian disimpulkan bahwa pesan dakwah tentang nikah yang diposting pengelola akun @nikahbarokah selama bulan Oktober sampai Desember 2016 terdapat 8 quote pesan dakwah diklasifikasikan berdasarkan tahap pernikahan yaitu taaruf, nikah dan pasca nikah dalam aspek fisiologis (sakinah), psikologis (mawadah), dan sosiologis (rahmah). Secara denotatif postingan yang terdapat pada gambar mengandung unsur gambar, tulisan kata-kata dan secara konotatif yang berkaitan dengan makna yang terdapat pada denotasi, dan secara makna mitos yang berkaitan dengan kehidupan sehari-hari.